ANALISIS MINAT MENABUNG DI KALANGAN SISWA SMA NEGERI DI KOTA MEDAN - Annisa Sabrina Dakhi; Irsyad Lubis (Departemen Ekonomi Pembangunan USU, 2014)
This research aims to study the condition of saving interest of student of SMAN in Medan. The type of this research is quantitative descriptive. There are 21 SMAN in Medan. The result of research indicates that the saving interest of student of SMAN in Medan city is lower because the research found that 77 respondents of 100 respondents have not saving in bank. This caused by their pocked money is few so they can not save their money in bank. However, most of them are saving their money at home. While the saving product known by students of SMAN in Medan is Britama Junio from BRI for 79 respondents and followed by BNI Taplus Muda from BNI for 74 respondents, and Tabunganku from Mandiri Bank for 61 respondent. The main reason for saving in bank is dominated by the future need for 11 students from 23 students who have saving in bank.Key words: Saving Interest, SMAN Student, and Bank